Sagot :
Answer:
Answer:
1. x = 120
2. x = -3
3. y = 10
Step-by-step explanation:
1. x varies jointly as y and z
x = kyz where k is the constant of variation
if x = 12, y = 1 and z = 6
x = kyz
12 = k ( 1 ) ( 6 )
12 = k ( 6 )
k = 12/6
k = 2
find x if y = 6 and z = 10.
x = kyz
x = ( 2 ) ( 6 ) ( 10 )
x = ( 12 ) ( 10 )
x = 120
2. z varies jointly as x and y
z = kxy where k is the constant of variation
if z = I, y = 2 and x = -3
z = kxy
( 1 ) = k ( -3 ) ( 2 )
1 = k ( -6 )
k = 1/( -6 )
k = -1/6
find x if z = 2 and y = 4
z = kxy
( 2 ) = ( -1/6 ) ( x ) ( 4 )
2 = x ( -4/6 )
2 = x ( -2/3 )
x = 2/( -2/3 )
x = 2 * ( -3/2 )
x = -6/2
x = -3
3. x varies directly as y and inversely as z
x = ky/z where k is the constant of variation
if x = 30, y = 2 and z = 3
x = ky/z
( 30 ) = k ( 2 )/( 3 )
30 = k ( 2 )/3
( 30 ) ( 3 ) = k ( 2 )
k ( 2 ) = 90
k = 90/2
k = 45
find y if z = 15 and x = 30.
x = ky/z
( 30 ) = ( 45 ) y/( 15 )
30 = 3 ( y )
y = 30/3
y = 10